Deflection ductility index in continuous reinforced concrete beams and slabs - José Santos (2013)
The behaviour of continuous reinforced concrete elements subjected to bending is characterized by a non-linear response whose extent depends on the available rotation capacity. In this paper the rotation capacity is reviewed and a numerical study for calculating the deflection ductility index in continuous reinforced concrete beams or one way spanning slabs is presented. The results indicate comfortable values between 1.0 and 2.0 for current beams used on building construction, while for slabs with high redistribution the limit values of slenderness and mechanical reinforcement ratios require some attention because slabs may not reach its total loading capacity.